If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 14x + 25 Reorder the terms: -5 + 6x = 14x + 25 Reorder the terms: -5 + 6x = 25 + 14x Solving -5 + 6x = 25 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -5 + 6x + -14x = 25 + 14x + -14x Combine like terms: 6x + -14x = -8x -5 + -8x = 25 + 14x + -14x Combine like terms: 14x + -14x = 0 -5 + -8x = 25 + 0 -5 + -8x = 25 Add '5' to each side of the equation. -5 + 5 + -8x = 25 + 5 Combine like terms: -5 + 5 = 0 0 + -8x = 25 + 5 -8x = 25 + 5 Combine like terms: 25 + 5 = 30 -8x = 30 Divide each side by '-8'. x = -3.75 Simplifying x = -3.75
| 7t+7=21 | | 2(lnx^3)-lnx+3=7 | | 3x+6y=92 | | 3k+1=40 | | 7e+3=45 | | 2(9-6)+y=12 | | 4(x+9)=3(x-8)+x | | -2(t+2)+5*t=6t+11 | | 5s+17=157 | | 7h+4=7 | | 2.4=2+0.3x | | 7p^2+6=0 | | X-4x=231 | | 2cosx=x | | 4*(d-3)=2d | | 9x-2y=-18 | | 8x^3-28x+29=0 | | 93+12m=3(4m-1) | | W^2+w+56= | | 6cos^2x-7cosX-10=0 | | 13=10n+6 | | 15*m=5 | | x+ln((x^2)-4)=0 | | 2x^2+12x+50=0 | | 2-4=4(2)-10 | | 4+7f=4 | | 120x+320=30-(x-3) | | q*q=15+1 | | factorx^2+12x+2=0 | | 120x+320=0.3-(x-3) | | 100x+700=60(x-3) | | 10x+35=6-(x-3) |